Abnormal neural circuits and altered brain network topological properties in patients with persistent postural-perceptual dizziness - Kangzhi Li; Xia Ling; Jing Zhao; Zhiqun Wang; Xu Yang (Communications Biology)
Abstract Persistent Postural-Perceptual Dizziness (PPPD) is a common cause of chronic vestibular syndrome. Although previous studies have identified central abnormalities in PPPD, the specific neural circuits and the alterations in brain network topological properties, and their association with dizziness and postural instability in PPPD remain unclear. This study includes 30 PPPD patients and 30 healthy controls. Resting-state functional magnetic resonance imaging is used to construct whole-brain functional connectivity matrices, followed by network-based statistic and graph theoretical analysis. Network-based statistic results reveal an abnormal neural network in PPPD patients with key nodes in the occipital visual cortex, precuneus, sensorimotor cortex, multisensory vestibular cortex and cerebellum. The graph theoretical analysis shows less efficient information transmission at both local and global levels, indicating a state of disconnection between regions of the brain network. Decreased connections between the visual cortex, sensorimotor cortex, and multisensory vestibular cortex, and changes in brain network topological properties are correlated with the Dizziness Handicap Inventory score. Our study unveils the potential abnormal neural circuits, with the presence of multisensory and sensorimotor integration abnormalities and reveals altered brain network topological properties in PPPD patients. Our findings provide new insights for understanding the neural mechanisms of PPPD.